Risk Factors for Anxiety and Depressive Symptoms in Doctors During the Coronavirus Disease 2019 Pandemic - He, Lanying; Wang, Jian; Zhang, Lijuan; Wang, Feng; Dong, Weiwei; Zhao, Wang (Frontiers in Psychiatry, 2021)
Background: The purpose of our study was to investigate the prevalence of anxiety and depressive symptoms and their risk factors among doctors during the coronavirus disease 2019 (COVID-19) pandemic. Methods: A hospital-based survey study was conducted. Anxiety symptoms were assessed using the Self-Rating Anxiety Scale (SAS), and depressive symptoms were assessed using the Self-Rating Depression Scale (SDS). Multivariable logistic regression was used to analyze anxiety and depressive symptoms across independent variables. Results: A total of 1,521 doctors were included; 11.11% (169/1,521) of the doctors had anxiety symptoms, and 16.90% (257/1,521) had depressive symptoms. Female sex [adjusted odds ratio (aOR), 1.69; 95% confidence interval (CI), 1.21–2.34; P = 0.002] and having a minor child (aOR, 2.31; 95% CI, 1.50–3.56; P < 0.001) were associated with an increased risk of anxiety symptoms. Female sex (aOR, 1.56; 95% CI, 1.18–2.06; P = 0.002) and having a minor child (aOR, 1.48; 95% CI, 1.06–2.01; P = 0.022) were associated with an increased risk of depressive symptoms. Older age (aOR, 0.97; 95% CI, 0.98–0.99; P = 0.008) was associated with a decreased risk of depressive symptoms. Conclusions: Anxiety and depressive symptoms have been common mental health problems in doctors during the COVID-19 pandemic. We found that female sex, having a minor child, and younger age were major risk factors for the development of anxiety and depressive symptoms among doctors during the COVID-19 pandemic.